STRATEGI PENINGKATAN KINERJA PELAYANAN PUBLIK (STUDI KASUS DI KANTOR CAMAT ASPARAGA KABUPATEN GORONTALO) - Puhi, Rahmawati; Suprapto, Srihandayani; Botutihe, Nuzlan (Gapenas Publisher, 2025)
The purpose of this research is to find out how to find out the Strategy for Improving Public Service Performance (Case Study at the Asparaga District Head Office, Gorontalo Regency). This research uses a descriptive method with a qualitative approach. The results of the research using Ida Yunari Ristiani's theory (2020) regarding service standard indicators then the results of the SWOT analysis show that there is a need to improve service performance carried out by the government of the Asparaga Subdistrict Office in the service process. This can be seen in the inadequate availability of apparatus resources and limited service facilities and infrastructure, resulting in services at the Asparaga Subdistrict Office being ineffective